UPAYA PERPUSTAKAAN MEWUJUDKAN RUANG PUBLIK INKLUSIF MELALUI LAYANAN HUMAN LIBRARY - Al-Ghiffary, Ghalib Muhammad Syukri; Dewi, Shinta; Yunus, Muhammad (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to examine the role of libraries as public spaces in promoting inclusivity through the implementation of the Human Library service. The Human Library is developed as a strategic innovation to reduce stigmatization and stereotypes against minority groups and marginalized communities. This research employs a literature study method by systematically analyzing various scholarly works and relevant literature related to the research topic. The data analysis process involves the collection of literature, selection of credible sources, identification of key issues, interpretation of findings, and comprehensive data presentation. The results indicate that libraries, as public spaces, play a significant role in fostering an inclusive environment through the Human Library service. Libraries are no longer merely repositories of collections but have transformed into spaces for interaction, sharing of experiences, and fostering mutual understanding among individuals from diverse backgrounds, identities, and life experiences